Tradycje związane z domem wiejskim utrwalone w relacjach mieszkańców Spisza - Helena Grochola; Anna Kostecka-Sadowa (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica)
The article presents a traditional image of a country home in Spisz. The material basis is the electronic corpus of rural speech (Korpus Spiski 2015–2019). The collocations of the lemmas: dom, chałupa, izba were observed during the analysis of corpus materials. The study of collocations allows us to clarify the semantics of lexemes. The names dom and chałupa have a characteristic dialectal understanding: ‘a rural farm belonging to one owner, including farm buildings, animals and equipment’. This meaning does not occur in the noun izba. Semantic and pragmatic structures describing traditional elements and forms of life associated with a country home were extracted from broader contexts. The traditional image of the Spisz home reveals two profiles: physical (residential building, farm) and symbolic (center of community family life, place of important events and celebrations, farm work, neighborhood meetings). Finally, the transformations that have taken place in the farmhouse are mentioned.